PERCEPTIONS OF COMMUNICATION SCIENCE STUDENTS CLASS OF 2018 TOWARDS THE TIK TOK APPLICATION AS A MEDIUM FOR SOMEONE'S POPULARITY - Asih Permata Bunda BR Ginting; Muhammad Alfikri (Universitas Dharmawangsa, 2022)
Increasingly sophisticated technology never satisfies desires and even encougares human curiosly. One of the influences of technology that cannot be separated from life is social media. Moreover, social media can help someone become famous. So this becomes a special attraction for pandemic, the TiokTok application was paresent in the midst of the community to accompany when rsearcherswant to find out how students perceive the application.